The importance of programmatic health actions in tuberculosis control: experience of a Primary Health Care Service in Porto Alegre, Rio Grande do Sul, Brazil - Camila Furtado de Souza; Ângela Jornada Ben; Silvete Maria Brandão Schneider; Bianca Peixoto Nascimento; Cristina Rolim Neumann; Francisco Jorge Arsego Quadros de Oliveira (Clinical and Biomedical Research, 2014)
Introduction: Tuberculosis deserves special attention from health professionals and society. However, health services are not organized to attend these patients, and the prevalence of the disease remains high in the country. The objective of this paper is to demonstrate the role of primary care in improving tuberculosis indicators with structured programmatic actions.